Transformation of Character Education in Elementary Schools Through the Merdeka Curriculum and the Project for Strengthening the Pancasila Student Profile - Dewi, Nastitisari; Marini, Arita; Zakiah, Linda (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
The transformation of character education at the elementary school level through the implementation of the Merdeka Curriculum and the Pancasila Student Profile Solidification Project aims to support character values which are an important foundation for individual development. The aim of this research is to conceptually describe how character education has changed at the elementary school level through the implementation of the Merdeka curriculum and the project to strengthen the profile of Pancasila students (P5). In this context, the Merdeka Curriculum provides greater flexibility in integrating character learning with academic material, while the Strengthening Pancasila Student Profile Project emphasizes foundational skills such as literacy, numeracy, and concrete Pancasila Student Character. This research outlines concrete steps in implementing these two initiatives in the elementary school environment and their positive impact on student character formation. This research uses a literature study research method (Library Research). The data collection technique in this article is reviewing journals, books, references and field studies that are appropriate to the research problem. The results of this research are 1) Study of the Implementation of the Independent Curriculum in the transformation of Character Education; 2) Study of the implementation of P5 in concrete steps for character formation in elementary school students; 3) Concrete steps that can be implemented as a manifestation of the transformation of character education in the Merdeka and P5 curriculum. Further research is needed to evaluate the overall and long-term effectiveness of implementing this curriculum.